2021
DOI: 10.35188/unu-wider/2021/111-2
|View full text |Cite
|
Sign up to set email alerts
|

The gender employment gap: the effects of extended maternity leave policy in Viet Nam

Abstract: UNU-WIDER employs a fair use policy for reasonable reproduction of UNU-WIDER copyrighted content-such as the reproduction of a table or a figure, and/or text not exceeding 400 words-with due acknowledgement of the original source, without requiring explicit permission from the copyright holder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…For example, while Aisenbrey et al ( 2009) use cross-country data for quantitative analysis and demonstrate the negative impact of extended leave on women's career development, Vu and Glewwe (2022) focus their study on a single country, Vietnam, and conclude that extended the leave duration does not increase the gender employment gap. While some scholars have demonstrated that ML can induce women to enter the labour market (Hanel, 2012), others have argued that because of ML, employers may be reluctant to hire women who have children or who intend to have them soon (Le and Pham, 2021). Similar differences also appear in the literature related to women's economic treatment, gender norms, and employment choices (see Table 2).…”
Section: Literature Reviewmentioning
confidence: 78%
See 4 more Smart Citations
“…For example, while Aisenbrey et al ( 2009) use cross-country data for quantitative analysis and demonstrate the negative impact of extended leave on women's career development, Vu and Glewwe (2022) focus their study on a single country, Vietnam, and conclude that extended the leave duration does not increase the gender employment gap. While some scholars have demonstrated that ML can induce women to enter the labour market (Hanel, 2012), others have argued that because of ML, employers may be reluctant to hire women who have children or who intend to have them soon (Le and Pham, 2021). Similar differences also appear in the literature related to women's economic treatment, gender norms, and employment choices (see Table 2).…”
Section: Literature Reviewmentioning
confidence: 78%
“…Furthermore, when employers are required to pay wages or other financial benefits during women on leave with no or little government contribution (Karshenas et al, 2014), these additional costs all lead to increased employment expenses for women (Del Boca et al, 2008;Low & Sá nchez-Marcos, 2015). Considering the costs associated with ML, employers may be reluctant to hire women who have children or who intend to have them soon (Le and Pham, 2021), this will prevent women from entering the labour market.…”
Section: Flfprmentioning
confidence: 99%
See 3 more Smart Citations